Short Excited‐State Lifetimes Mediate Charge‐Recombination Losses in Organic Solar Cell Blends with Low Charge‐Transfer Driving Force. Issue 22 (15th August 2021) - Shivhare, Rishi; Moore, Gareth John; Hofacker, Andreas; Hutsch, Sebastian; Zhong, Yufei; Hambsch, Mike; Erdmann, Tim; Kiriy, Anton; Mannsfeld, Stefan C. B.; Ortmann, Frank; Banerji, Natalie
Abstract: A blend of a low‐optical‐gap diketopyrrolopyrrole polymer and a fullerene derivative, with near‐zero driving force for electron transfer, is investigated. Using femtosecond transient absorption and electroabsorption spectroscopy, the charge transfer (CT) and recombination dynamics as well as the early‐time transport are quantified. Electron transfer is ultrafast, consistent with a Marcus–Levich–Jortner description. However, significant charge recombination and unusually short excited (S1 ) and CT state lifetimes (≈14 ps) are observed. At low S1 –CT offset, a short S1 lifetime mediates charge recombination because: i) back‐transfer from the CT to the S1 state followed by S1 recombination occurs and ii) additional S1 –CT hybridization decreases the CT lifetime. Both effects are confirmed by density functional theory calculations. In addition, relatively slow (tens of picoseconds) dissociation of charges from the CT state is observed, due to low local charge mobility. Simulations using a four‐state kinetic model entailing the effects of energetic disorder reveal that the free charge yield can be increased from the observed 12% to 60% by increasing the S1 and CT lifetimes to 150 ps. Alternatively, decreasing the interfacial CT state disorder while increasing bulk disorder of free charges enhances the yield to 65% in spite of the short lifetimes. Abstract : Organic solar cells that employ donor:acceptor blends with near‐zero driving force for charge transfer are becoming prevalent because of their superior performance. In this work, the factors affecting charge transfer and subsequent dissociation of the charge‐transfer state are experimentally and theoretically analyzed. Short excited‐state lifetime and hybridization open up new recombination channels with detrimental effects on free‐charge generation.